Au-O-MWCNTs and TiO2-O-MWCNTs as Efficient Nanocarriers for Dexamethasone: Adsorption Isotherms and Kinetic Studies. (21st September 2021) - Haghighi, Maryam; Khoshfetrat, Azadeh
Abstract : In this research, the fabrication of drug delivery systems based on oxidized multiwall carbon nanotubes (O-MWCNTs) was studied. Herein, TiO2 and Au were conjugated with O-MWCNTs to prepare efficient nanocarriers for dexamethasone (dex). The samples were characterized by Fourier transform infrared (FTIR), scanning electron microscopy (SEM), and X-ray diffraction (XRD). In addition, dex loading was studied using adsorption isotherms including Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich. The results show that dex adsorption agreed well with the Freundlich isotherm. Increasing the TiO2 to O-MWCNT ratio from (1 : 4) to (1 : 2) can improve the adsorption capacity from 290 mg ⋅ g − 1 to 320 320 mg ⋅ g − 1 . The increasing Au amount increases the adsorption capacity from 437.78 mg ⋅ g − 1 (SA1) to maximum 476.19 mg ⋅ g − 1 (SA6). The maximum equilibrium binding energy A T 1.67 L ⋅ mg − 1 was obtained for SA2, and SA7 shows high binding strength between dex and the nanoadsorbent. Carbon nanotubes (CNTs) show good affinity with high loading capabilities for dexamethasone adsorption. The synthesized TiO2 -O-MWCNTs:1/2 with the maximum removal percent (80%) was proposed as an appropriate nanocarrier for dexamethasone. Pseudo-first order, pseudo-second order, Elovich, and intraparticle diffusion models were investigated for all synthesized drug nanocarriers. According to regression coefficients, experimental data are in good agreement with the pseudo-second order model for all adsorbents except O-MWCNT/CTAB. Experimental results revealed that the Elovich model could account for the O-MWCNT/CTAB adsorbent.